The development and performance of European private equity. - Jenkinson, T (Oxford Finance, 2008)
In this paper we analyse the development of the European private equity sector: how it has grown, the distribution of investments, and the returns. From being a niche sector only a few years ago, the private equity sector within Europe has emerged from the shadows and is becoming increasingly the focus of attention. In part this is due to the sheer amount of capital being raised by the private equity sector.